2020
DOI: 10.1029/2020jb020570
|View full text |Cite
|
Sign up to set email alerts
|

Pore‐Scale 3D Morphological Modeling and Physical Characterization of Hydrate‐Bearing Sediment Based on Computed Tomography

Abstract: Natural gas hydrate is considered to be a promising future energy resource; therefore, obtaining its physical properties is crucial for evaluating gas production efficiency and developing reasonable exploitation strategies. In this study, we present a novel pore-scale 3D morphological modeling algorithm considering various saturation and occurrences (cementing and pore-filling) of hydrate in sediments. To evaluate the performance of the presented algorithm, 14 hydrate-bearing sediment models were constructed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 76 publications
1
38
0
Order By: Relevance
“…In addition, it has to be noted that although the median radii of the pore space in the two specimens are around 100 μm, the hydrate particle could be even larger than 10 mm 3 . This is because the hydrate particle is not an isolated small particle only existing in a single pore as the idealized conceptual model ( Clennell et al., 1999 ; Wu et al., 2020c ), but a cluster existing in multiple pores and throats at the same time.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has to be noted that although the median radii of the pore space in the two specimens are around 100 μm, the hydrate particle could be even larger than 10 mm 3 . This is because the hydrate particle is not an isolated small particle only existing in a single pore as the idealized conceptual model ( Clennell et al., 1999 ; Wu et al., 2020c ), but a cluster existing in multiple pores and throats at the same time.…”
Section: Resultsmentioning
confidence: 99%
“…A novel pore-scale 3D morphological modeling algorithm for hydrate generation proposed by Wu et al [24] was used in this study. As illustrated in Figure 2(b), the spe-cific steps are as follows: Firstly, conducting CT scanning for the host sediment.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, assembling the sand phase, hydrate phase, and corresponding pore phase for the image stacks of the pore-filling HBS. The more detailed introduction could be found in the morphological algorithm proposed by Wu et al [24]. In addition, the bulk variation since the hydrate generation is not considered, this is because Lee et al [27] found that during hydrate generation, the HBS's volumetric strain is only around 0.1% which could be insignificant.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations